Nuclear alterations in nasal mucosa epithelial cells of students exposed to formaldehyde - Leon Cleres Penido Pinheiro; Haniel Moraes Serpa Nascimento; Cristiani Sartorio Menegardo; Ronara Gerhardt Silva; Diego Coelho Lorenzoni; Leticia Nogueira da Gama de Souza
Introduction: Formaldehyde is a compound with a wide range and is commonly used in anatomy and pathology laboratories. At room temperature is quickly volatilized to a pungent and suffocating gas and its inhalation has been correlated to nuclear alterations in different tissues. We aimed to investigate whether exposure to this compound was correlated with the appearance of cytotoxic and genotoxic features in the nasal epithelial cells of students enrolled in a human anatomy course. Material and Methods: This prospective study collected periodically nasal cells from mucosa of 17 volunteers from two different undergraduate programs with different workloads of practical lessons in an anatomy laboratory, 30 and 90 hours per semester. Cells were staining according to Feulgen method and nuclear morphology was analyzed to detect possible damage. Dunn's post hoc test was used in the statistical analysis. Pearson's correlation was performed for gender, age and questionnaire responses. Results: Epithelial cells showed indicators of cytotoxicity and mutagenicity. Students with a more extensive workload in anatomy laboratory displayed a more severe profile with an increase in karyorrhexis (p < 0.05) over time. The micronucleus analysis showed difference between first and second collection (p < 0.01), although it was not maintained over the time. Students with a less extensive workload display no differences in most of cytological features. Despite karyorrhexis was present in a greater number of cells, for this group no significant difference was observed between any range. The same was observed to karyolysis and micronucleus (p > 0.05). Conclusion: Individuals exposed for short periods of time to formaldehyde are subject to the toxic action of this gas. Karyorrhexis was the most frequently observed cytotoxic feature and micronucleus showed an increase between the first time point. The patterns observed between the student's groups suggest a negative effect due to exposure time.